2023
DOI: 10.1108/ijis-12-2022-0244
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of precursors of online impulse buying and its effects on purchase regret: role of consumer innovation

Abstract: Purpose Impulsive buyers are a dream segment for retailers and marketers. Stimulants in the retail environment and cognitive aspects evoke a sudden urge the acquisition of products spontaneously. This paper aims to examine key cognitive aspects of impulsive buying behaviour and purchase regret in an online context. Design/methodology/approach An online survey was conducted to collect the data of 317 online consumers with the help of a convenience sampling technique. The structural equation modelling techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The benign embrace of a shopping haven, bedecked with the harmonious convergence of music, hues painting the canvas, and fragrant whispers, acts as a nurturing cradle fostering the impetus for impulsive purchases (Chen and Yue 2023). It's within the sanctum of these store environs that the humdrum routines of purchases metamorphose into exhilarating escapades, pulsating with the thrill of spontaneity and excitement (Sarwar et al 2023). Furthermore, the external echo of sales promotions and the irresistible allure of discounted prices stand as beckoning sirens goading consumer impulses towards impromptu acquisitions (Lou et al 2022).…”
Section: Effect Of Sensation Cues On Impulse Buying Behaviormentioning
confidence: 99%
“…The benign embrace of a shopping haven, bedecked with the harmonious convergence of music, hues painting the canvas, and fragrant whispers, acts as a nurturing cradle fostering the impetus for impulsive purchases (Chen and Yue 2023). It's within the sanctum of these store environs that the humdrum routines of purchases metamorphose into exhilarating escapades, pulsating with the thrill of spontaneity and excitement (Sarwar et al 2023). Furthermore, the external echo of sales promotions and the irresistible allure of discounted prices stand as beckoning sirens goading consumer impulses towards impromptu acquisitions (Lou et al 2022).…”
Section: Effect Of Sensation Cues On Impulse Buying Behaviormentioning
confidence: 99%
“…In the research on consumption behavior that evokes negative emotions, Crusius and Mussweiler (2012) found that upward comparisons can lead to impulse consumption [6]. This consumption behavior can arouse negative emotions such as anxiety and regret [7]. In addition, Zheng et al (2020) showed that upward com-parisons can lead to compulsive consumption [9].…”
Section: Upward Comparisonmentioning
confidence: 99%
“…Scholars have examined the effects of upward comparisons on consumption behavior that evokes either positive or negative emotions. In research on consumption behaviors that can evoke negative emotions, scholars found that upward comparisons can lead to impulse consumption that can arouse negative emotions such as anxiety and regret [6,7], compulsive consumption that can arouse anxiety and regret [8,9], and indulgent food consumption that can awaken anxiety and guilt [10,11]. In research on consumption behaviors that can evoke positive emotions, scholars examined the effect of upward comparison on donation behavior that can improve self-esteem and increase well-being [12,13] and sustainable consumption that can make consumers feel pleasure [14,15].…”
Section: Introductionmentioning
confidence: 99%